A qualitative study exploring the acceptability of the TEXTPAD telehealth and virtual supervised exercise intervention and trial for patients with peripheral arterial disease living in socioeconomically disadvantaged areas - Maddey Patterson, MPH; Letitia Sermin-Reed, MSc; James Prentis, MBBS; Arathi Radhakrishnan, MBBS; Eileen Kaner, PhD; Sandip Nandhra, MBBS; Maisie Rowland, BSc; Gabriel Cucato, PhD; Mackenzie Fong, PhD (JVS-Vascular Insights)
Background: UK clinical guidelines recommend supervised exercise training and support for health behavior change for patients with peripheral arterial disease (PAD). Despite this, supervised exercise programs are largely unavailable and unfunded across the UK. Remote, virtual support may overcome some barriers to attending facilities in person experienced by PAD patients, such as poor mobility and financial cost. The TEXTPAD pilot randomized controlled trial investigated the impact of the 12-week TEXTPAD intervention that involved weekly phone calls for behavioral counselling and twice-weekly virtual, supervised exercise sessions. Both TEXTPAD and control group participants were encouraged to engage in an unsupervised walking program and were provided with an activity tracker. This qualitative study aimed to explore participants' acceptance of the TEXTPAD and unsupervised walking programs and trial procedures. Methods: Participants were recruited from the vascular department of Newcastle-upon-Tyne Hospitals Trust. Eligibility for the pilot randomized controlled trial included age ≥40 years, a diagnosis of PAD, and living in an area in the lowest 30% of super output area based on the Office for National Statistics. Interview participants were sampled purposively based on study group allocation. A focus group was conducted with three health improvement practitioners who delivered the TEXTPAD intervention. Interview and focus group audio recordings were transcribed verbatim and thematic analysis was applied to data. Results: A total of 18 participants were interviewed, comprising 9 participants each in the TEXTPAD and control groups (mean age, 66.2 years). Fifteen patients were male and three were female. Overall, the TEXTPAD and walking programs were highly acceptable to and positively perceived by participants. Some participants were not confident in using the various aspects of technology needed to engage in the TEXTPAD and walking programs and sought support from family, friends, or practitioners. TEXTPAD participants wanted more interaction with other participants to share experiences, advice, and information (theme 1). Participants in both groups perceived a range of benefits to their health and well-being (theme 2) and considered the study procedures to be acceptable and not overly burdensome (theme 3). Conclusions: Providing exercise training and behavioral counselling virtually using digital technologies to people with PAD from lower socioeconomic backgrounds can be considered as an acceptable way to deliver care. However, people who have poorer digital skills must be provided with adequate support to use the technologies needed to engage with these virtual interventions. Enabling intervention participants to interact with each other would help to nurture social support which was perceived to be lacking in the current program.